Preliminary study on antifungal activity of pyroligneous acid from Rhizophora Apiculata / Noor Amira Muhammad, Saiyidah Nafisah Hashim and Siti Nur Azmu’i Abdullah - Muhammad, Noor Amira; Hashim, Saiyidah Nafisah; Abdullah, Siti Nur Azmu’i (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Pyroligneous acid is the name of the crude condensate produced from the distillation of smoke generated in the process of charcoal making. The antifungal activity of Rhizophora apiculata pyroligneous acid was evaluated. Pathogenic fungi was firstly taken from the infected leaves of untreated chilli plant and cultured on Potato Dextrose Agar (PDA). Purification of the culture was done by using pour plate method. The fungi morphology was further determined by using methylene blue under light microscope and was identified as Leveillula species. Leveillula sp. was successfully isolated and further cultured. Four different concentrations of pyroligneous acid (25, 50, 75 and 100 %) was mixed thoroughly with the molten agar using food poisoned technique. The antifungal activity was left for 72hours before the mycelial growth was measured. The results revealed that 50, 75 and 100% of pyroligneous acid showed significant antifungal activity towards Leveillula species with 100% of percentage inhibition. Hence, this study has proven that pyroligneous acid can be an alternative in agriculture as organic fungicide to combat L. taurica on chilli plants.